Introduction: a critique of digital practices and research infrastructures - Champion, Erik (Digital Research in the Arts and Humanities, 2017)
In this book authors from a wide range of countries, representing some of the best research projects in digital humanities related to cultural heritage discuss their latest findings, both in terms of new tools and archives, and how they are ...